New York : Treasures of the Museum of the City of New York. - Jaffe, Steven H.; Museum of the City of New York. (New York : Abbeville Press, 2020)
"Illustrates some 250 diverse items from the collections of the Museum of the City of New York"--Provided by publisher.
boek
Keywords: Museum of the City of New York -- Catalogs; New York (N.Y.) -- History